INFLUENCE OF ANALGESIC THERAPY ON THE AMPLIFICATION OF OROFACIAL PAIN: PHYSIOPATHOLOGICAL MECHANISMS - Dias Machado, Daniel (Health and Society, 2025)
This study addresses the influence of analgesic therapy on the amplification of orofacial pain, focusing on the pathophysiological mechanisms involving central sensitization and hyperalgesia in patients with chronic pain. Prolonged administration of analgesics, especially opioids, has been associated with the development of central sensitization, a process in which the central nervous system becomes more sensitive to painful stimuli, making pain more intense and harder to treat. Moreover, the continuous use of these medications can alter pain signaling pathways, such as the activation of NMDA receptors and the release of excitatory neurotransmitters, contributing to pain exacerbation. The impact of psychosocial comorbidities, such as anxiety and depression, was also analyzed, as these conditions can potentiate pain amplification, further complicating the management of orofacial pain. The study proposes the need for alternative or complementary therapeutic strategies, such as acupuncture and cognitive-behavioral therapy, to minimize the adverse effects of analgesic therapy and promote a more effective and safe treatment. A critical analysis of these mechanisms and the search for individualized approaches are essential for more efficient management of chronic orofacial pain.